AB0002 Sirt-1 Activity in PBMC from Patients with Spondyloarthritis. (10th June 2014) - Wendling, D.; Delattre, E.; Abbas, W.; Guillot, X.; Godfrin-Valnet, M.; Khan, K.A.; Toussirot, E.; Baud, L.; Prati, C.; Herbein, G.
Abstract : Background: Sirtuin 1 (Sirt1) is a nuclear enzyme from the class III histone deacetylases (HDACs) modulating gene expression, involved in the regulation of various biological processes (cell survival, apoptosis, gluconeogenesis, adipogenesis, lipolysis), local and systemic inflammation, as well as in bone and cartilage remodeling. Sirt-1 reduces pro inflammatory cytokines release. Spondyloarthritis (SpA) is a multifactorial disease, but no epigenetic data are currently available in this disease. Objectives: The main objective of the study was to evaluate Sirt1 activity in PBMC by venous blood aspiration in spondyloarthritis (SpA) patients, compared to those of control patients, and to analyze the relationship between Sirt1 activity, disease activity and production of mediators of inflammation and cytokines (TNFalpha, IL-6, IL-8) by the cells, before and after ex vivo treatment with a Sirtuin activator, resveratrol. Methods: A prospective and comparative monocentric study was performed in order to compare the activity of Sirt1 in patients with SpA (according to ASAS criteria) and controls. Disease activity was assessed by BASDAI, ASDAS, ESR and CRP. PBMC were isolated from venous blood, and Sirt1 activity was evaluated from cytoplasmic and nuclear compartments using a fluorometric assay (SIRT1 fluorimetric kit, BML-AK-555, Enzo Life Sciences, Villeurbanne, France) at the 15 minutes point. Culture supernatant levels of TNF alpha, IL-6, IL-8 were quantified before and after resveratrol (1 μmol and 5 μmol) ex vivo treatment, with commercial kits (Quantikine Kits, R&D Systems, Minneapolis, MN). Statistical analysis used Wilcoxon and t tests; significance: p less than 0.05. Results: Forteen patients with SpA (age 48±14 years, mean BASDAI 43±18; ASDAS-CRP 3, 1±0, 9; disease duration 19±10 years; all were HLA-B27+; mean CRP: 19.1 mg/l) and 18 controls (age 54±13 years) were included. No differences were found in cytoplasmic or nuclear Sirt1 activity between patients and controls. Cytoplasmic and nuclear Sirt1 activity were correlated each other in patients and controls. Sirt1 activity (nuclear and cytoplasmic) was not correlated with ASDAS, BASFI, CRP or ESR, but a trend of correlation was found between nuclear Sirt-1 activity and BASDAI (r =0.5; p=0.07). No differences in Sirt1 activity was found between axial and peripheral forms of SpA. Sirt1 activity (cytoplasmic and nuclear) was higher in SpA with NSAIDs compared to patients without NSAIDs (p=0.005). No correlations were found between Sirt1 activity and cytokine levels at baseline, and no change after ex vivo treatment by resveratrol. Conclusions: Sirt1 activity (cytoplasmic and nuclear) from PBMC was not different between SpA patients and controls in this study, these result do not argue for a major implication of Sirt1 in SpA. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1744